The horse and his boy - Lewis, C.S.; The Chronicles of Narnia (Lahore ILQA Publications, 2015)
(3z(BThe Horse and His Boy(3y (Bis the third Narnia book and the only one which is entirely set in the magical land and features natives as main characters. Shasta, a Calormene boy, leaves his home with his talking horse Bree for Narnia when he overhears his fraudulent father s plan to sell him off. On the way he meets a runaway girl Aravis and her talking horse Hwin. Aravis has escaped an undesirable marriage. The fate throws the four into a world of adventures, the last of which is a great battle whose outcome will determine their future lives.s
A classic of children s fantasy literature, (3z(BThe Chronicles of Narnia(3y (Bis a series of seven stand-alone books. It is one of the most popular children series ever written. It has been translated in more than 40 languages and sold over 100 million copies around the world.s
Keywords: Fiction & Literature/ Classic